Mahmudkhoja Behbudiy – A Leader of National Identity and Enlightenment (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is dedicated to illuminating the multifaceted activities of Mahmudkhoja Behbudiy, a thinker of the national revival period of the XX century, leader of the Turkestan Jadids, a public and religious figure, pedagogue, writer, publisher, and skilled publicist. The new ideas and goals promoted by this encyclopedic scholar in the educational system, press, literary processes, social and political life, and his worthy service for the prosperity of the nation and the homeland are presented.